2023
DOI: 10.1039/d3nr01400b
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in theoretical and experimental investigations on diamane materials

Bowen Liu,
Emilia Emmanuel,
Tao Liang
et al.

Abstract: Technology-driven modern civilization urgently needs new materials as a backbone. With the intense research, a promising candidate, diamane, a two-dimensional (2D) form of diamond with a bilayer sp3 carbon nanostructure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Diamane with different characteristics can be obtained by controlling the structural conformation and stacking sequence of graphene layers. ,, AB- and AA-stacked diamanes with chair-type conformation (Figure S1) have been experimentally synthesized, and their structural and electronic properties are extensively studied . Previous works revealed that the bandgap of structure with AB stacking is slightly larger than that of AA stacking. , Additionally, AB-stacked diamane has a lower formation energy compared to AA-stacked diamane, making it thermodynamically more stable. , In order to ensure the application of a gas sensor under complex conditions, stable AB-stacked diamane is selected to investigate the sensing performance in the following.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diamane with different characteristics can be obtained by controlling the structural conformation and stacking sequence of graphene layers. ,, AB- and AA-stacked diamanes with chair-type conformation (Figure S1) have been experimentally synthesized, and their structural and electronic properties are extensively studied . Previous works revealed that the bandgap of structure with AB stacking is slightly larger than that of AA stacking. , Additionally, AB-stacked diamane has a lower formation energy compared to AA-stacked diamane, making it thermodynamically more stable. , In order to ensure the application of a gas sensor under complex conditions, stable AB-stacked diamane is selected to investigate the sensing performance in the following.…”
Section: Resultsmentioning
confidence: 99%
“…23,43,44 AB-and AA-stacked diamanes with chair-type conformation (Figure S1) have been experimentally synthesized, and their structural and electronic properties are extensively studied. 45 Previous works revealed that the bandgap of structure with AB stacking is slightly larger than that of AA stacking. 46,47 Additionally, AB-stacked diamane has a lower formation energy compared to AA-stacked diamane, making it thermodynamically more stable.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Recent advancements in the synthesis and functionalization of 2D layer materials have enabled the development of more precise, efficient, and selective targeted therapy techniques to improve light-heat conversion efficiency ( Liu B. et al, 2023 ; Liu et al, 2023e ; Sutter and Sutter, 2023 ). By appropriate lamellar size stripping and surface molecular modification, 2D materials were effectively converged to the tumor site, albeit intravenously, followed by corresponding ablative therapy under direct vision.…”
Section: Cancer Inhibition With Energy Conversion and Dynamic Therapymentioning
confidence: 99%
“…It is discernible that while the synthesis of diamane, reliant on transcending the energy barriers associated with the transformation of sp2 to sp3 bonds under extreme pressure and temperature, is untenable under ambient conditions, surface chemical functionalization effectively diminishes these energy barriers, thereby substantially reducing the requisite transition pressure and augmenting the stability of diamane. 37 Furthermore, recent studies [38][39][40][41] have illuminated the possibility of utilizing boron and nitrogen doping to stabilize the structure of diamane and modulate its properties. Theoretical investigations by Pakornchote et al 40 propose that nitrogen substitution for the HCu of H-diamane can maintain its structural integrity, enhancing the non-inert stability of diamond-like carbon films, referred to as NCCN.…”
Section: Introductionmentioning
confidence: 99%